Back Matter Jurnal Litbang Industri Vol. 10 No. 1 Juni Tahun 2020 - Sofyan Sofyan (Institution for Industrial Research and Standardization of Industry - Padang, 2020)
Back Matter Jurnal Litbang Industri Vol. 10 No. 1 Juni Tahun 2020